Living plant energy harvesting for WSN & IoT devices - Mohd Taam, Ahmad Zun Najhi; Habaebi, Mohamed Hadi; Islam, Md. Rafiqul (IEEE, 2024)
A Wireless Sensor Network (WSN) is a wireless network that consists of sensor nodes that were installed at a variety of places including on trees, near the river, on cliffs, and even under the ground. These sensors will be scheduled to gather some data and forward them to the nearest network gateway. The sensor nodes use a wireless communication protocol known as Low Power Wide Area Network (LPWAN) that can transfer data at a very long range of up to 10km using a minimum power supply, making it suitable for monitoring environmental events in Malaysian forests. Currently, most sensor nodes are operated using batteries which means that they need to be replaced once the batteries die out. Changing sensor nodes’ batteries can be cost-prohibitive and dangerous depending on the circumstances. An alternative solution is to harvest energy from the forest living plants themselves which have been proven to store electrical energy in the form of electrolytes. This work introduces a field study that attempts to quantify and analyze the amount of energy harvested from local forest living plants in Malaysia to power up the sensor nodes.